Evaluation of Jordan's citizens' awareness of the emerging Coronavirus (COVID-19) disease: A mixed analysis of the symptoms, transmission, and preventive measures. - Inas Almazari; Roba Bdeir; Haneen A Basheer (Public Library of Science (PLoS), 2022)
This study aimed to evaluate Jordan citizens' awareness, knowledge, and practice concerning Coronavirus-19 (COVID-19) symptoms, routes of transmission, and preventive measures. An online self-administered questionnaire was filled out completely by participants (N = 328) from mainly four major cities in Jordan during the period beginning of May-end of September 2020. Participants' main sources of knowledge about COVID-19 were the government websites (87.8%), social media (87.5%), and Television (TV) (81.1%). The majority of participants valued the drizzle of cough from infected individuals (96.3%), direct contact with contaminated surfaces (91.5%), and direct contact with infected individuals (84.5%) as the highest rates of the route of transmission. The highest rates chosen as symptoms of COVID-19 viral infections were high-grade fever (99.1%), troublesome breathing (96.6%), coughing (92.7%), headache (91.2%), and loss of smell and taste (80.8%). The majority of participants (>92%) strongly agreed on the behavioral protective measures such as no face touching, wearing a mask, the use of alcoholic hand disinfectants, and the need for self-isolation. This study showed that the Jordanian citizens were aware of the epidemiology of COVID-19 and related infection preventive measures. This agrees well with the efforts done by the Ministry of health and governmental organizations to spread the necessary information about the virus among citizens.